Lead exposure is non-linearly associated with subclinical myocardial injury in the general population without cardiovascular disease - Wang, Zhenwei; Huang, Xu; Li, Jingjie; Liu, Naifeng; Wei, Qin (Frontiers in Public Health, 2022)
Background and aims: Growing studies have focused on the effect of lead exposure on human circulatory system, while the relationship between lead exposure and subclinical myocardial injury (SC-MI) is still poorly known. Therefore, this study was to explore the effect of lead exposure on SC-MI. Methods: The study included 6,272 individuals aged 40 and older without cardiovascular disease (CVD) from the third National Health and Nutrition Examination Survey. Blood lead was used as an alternative marker of lead exposure. Multivariable logistic regression models, restricted cubic spline and threshold effect analyses were performed to investigate the effect of blood lead on SC-MI. Results: After adjusting for age, sex, race, diabetes, hypertension, systolic blood pressure, body mass index, waist-to-hip ratio, triglycerides, total cholesterol, creatinine, fasting plasma glucose and hemoglobin Alc, higher blood lead level was independently related to higher risk of SC-MI (OR 1.047, 95 % CI [1.018, 1.077]; P = 0.003). Restricted cubic spline curve showed that there was a nonlinear correlation between blood lead and SC-MI. Threshold effect analysis determined that the inflection point of blood lead was 3.8 ug/dl. When the blood lead level was higher than 3.8 ug/dl, there was an independent positive correlation between blood lead level and the risk of SC-MI (OR 1.031, 95 % CI [1.009, 1.053]; P < 0.01). And similar associations were also observed among subgroups of male, ≤ 60 years, > 60 years, never smoker, non-Hispanic White, non-Hispanic Black or without hypertension and diabetes. Conclusions: Blood lead was nonlinearly related to SC-MI in population free from CVD.